SOCIO-TOWN-PLANNING BACKGROUND RENOVATION OF PUBLIC SPACES IN THE URBAN ENVIRONMENT (Municipal economy of cities. Series: «Economy science», 2013)
Defined social and urban prerequisites of public spaces renovation in the urban environment including the complex influencing factors.